2007
DOI: 10.1590/s0100-67622007000400006
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da luminosidade e da adição de nitrogênio no crescimento de plantas de Ilex paraguariensis St. Hil.

Abstract: Neste trabalho, buscou-se identificar o efeito de diferentes níveis de luminosidade e da adição de adubo nitrogenado sobre o crescimento das plantas de erva-mate, no primeiro ano de crescimento. No experimento, usou-se o delineamento de blocos ao acaso, com três repetições, em quatro tratamentos e dois subtratamentos, tendo 16 parcelas por bloco. O esquema adotado foi o fatorial, tendo como variável constante a luminosidade em quatro intensidades (100, 70, 50 e 30%) e o nitrogênio como variável interveniente s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
1
0
1
5
Order By: Relevance
“…In the area of Lebon Régis, the treatment of 0-20 % cover showed plants with the greatest height when compared with the intermediate treatment (20-40 %), which did not differ from the treatment of 40-60 % cover. This behavior differs from the results reported by several authors (DA SILVA et al, 2007;MAZUCHOWSKI et al, 2007), which identified the greatest heights in seedlings exposed to intense shading. In these studies, the observed behavior is justified by a phenomenon known as Shade-avoidance Syndrome (SAS), as described by Ballaré (2014), when plants are exposed to shading conditions based on the response of photoreceptors, a series of reactions start and they result in the transcription of growth-promoting hormones.…”
Section: Yerba Matecontrasting
confidence: 99%
“…In the area of Lebon Régis, the treatment of 0-20 % cover showed plants with the greatest height when compared with the intermediate treatment (20-40 %), which did not differ from the treatment of 40-60 % cover. This behavior differs from the results reported by several authors (DA SILVA et al, 2007;MAZUCHOWSKI et al, 2007), which identified the greatest heights in seedlings exposed to intense shading. In these studies, the observed behavior is justified by a phenomenon known as Shade-avoidance Syndrome (SAS), as described by Ballaré (2014), when plants are exposed to shading conditions based on the response of photoreceptors, a series of reactions start and they result in the transcription of growth-promoting hormones.…”
Section: Yerba Matecontrasting
confidence: 99%
“…They further state that that there is a nursery effect on survival and early growth of seedlings in the field. This behavior is in agreement with Lemos et al (2007) and Mazuchowski et al (2007), who suggest that the increased rate of stem elongation occurs in proportion to the level of shading. Morais et al (2003) found a greater height growth of the coffee (Coffea arabica L.) under shade of gandu (Cajanus cajan (L.) Millsp.…”
supporting
confidence: 93%
“…Cada compartimento foi posto em sacos de papel devidamente identificados, sendo estes levados à estufa de circulação forçada na temperatura de 60 °C até atingir peso constante (SILVA et al, 2007;RESENDE et al, 2011). Posteriormente, pesou-se o material em balança de precisão, para obtenção do peso da matéria seca.…”
Section: Methodsunclassified